Entrepreneurship and economic growth in the American economy - Libecap, Gary D. (Advances in the study of entrepreneurship, innovation and economic growth ;, 2000)
This volume includes a series of papers which examine the contributions of entrepreneurship education on the performance of graduates. Using survey data for 2,484 entrepreneurship and non-entrepreneurship graduates, the analysis indicates that entrepreneurship education contributes to risk taking, the formation of new ventures, and firm growth. The second chapter continues with an assessment of the effects of entrepreneurship and technological change historically, focusing on the computer industry. Chapter three also examines the development of property rights in the computing industry with an assessment of the special problems of the internet. Chapter four turns to broader questions of the bases for entrepreneurial behavior within firms and presents survey data from South Africa and the US. Chapter five continues the analysis of entrepreneurial activities. A model is presented and implications are drawn. The final two chapters examine specific marketing issues for entrepreneurial firms. With ease of entry and intense competition, marketing strategies become especially critical.